A cross-priming amplification assay coupled with vertical flow visualization for detection of Vibrio parahaemolyticus. Issue 6 (December 2015) - Xu, Deshun; Wu, Xiaofang; Han, Jiankang; Chen, Liping; Ji, Lei; yan, Wei; Shen, Yuehua
Abstract: Vibrio parahaemolyticus is a marine seafood-borne pathogen that causes gastrointestinal disorders in humans. In this study, we developed a cross-priming amplification (CPA) assay coupled with vertical flow (VF) visualization for rapid and sensitive detection of V . parahaemolyticus . This assay correctly detected all target strains (n = 13) and none of the non-target strains (n = 27). Small concentrations of V . parahaemolyticus (1.8 CFU/mL for pure cultures and 18 CFU/g for reconstituted samples) were detected within 1 h. CPA-VF can be applied at a large scale and can be used to detect V . parahaemolyticus strains rapidly in seafood and environmental samples, being especially useful in the field. Highlights: This detection method can be applied in field since the system only needs some simple equipments. The sealing device avoids cross-contamination between specimens, and the results are easy to interpret. This CPA-VF method is high sensitivity and specificity for the identification of V. parahaemolyticus in seafood samples.